Taste Detection Thresholds in Relation to Salivary and Serum Zinc in Patients on Simvastatin Treatment - Hassanien J. Mohammed; Taghreed F. Zaidan (College of Dentistry/ University of Baghdad, 2019)
Background: Hyperlipidemia is an elevated fat (lipids), mostly cholesterol and triglycerides, in the blood. These lipids usually bind to proteins to remain circulated so-called lipoprotein. Aims of the study: To determine taste detection threshold and estimate the trace elements (zinc) in serum and saliva of those patients and compare all of these with healthy control subjects. Methods: Eighty subjects were incorporated in this study, thy were divided into two groups: forty patients on simvastatin treatment age between (35-60) years, and forty healthy control of age range between (35-60) years. Saliva was collected by non-stimulated technique within 10 minutes. Serum was obtained from each subject. Zinc was estimated in serum and saliva by flame atomic absorption assay. Taste detection threshold was estimated by using 15 different concentrations of the four basic tastes solutions, the test use sip and spit with deionized water as mouth wash interval. Diabetics, thyroid and parathyroid disease, autoimmune disease, chemotherapy, smoking, alcoholics, neoplastic diseases were excluded. Results: The study showed that the taste detection threshold of sour and bitter were highly significantly higher in those patients than that in control subjects, sweet detection threshold were significantly high in patient on simvastatin. The salt detection threshold showed no significant differences between study groups. Salivary flow rate was significantly decreased in patients on simvastatin treatment than that in control subjects. Salivary and serum zinc were highly significantly decreased in control subjects than those in patients. There was highly significantly positive linear correlation between salivary flow rate and the mean of detection threshold of sweetness and sourness of both study groups, and highly significantly negative linear correlation with the mean of detection threshold of saltiness and bitterness in both study groups.